Applied psychology : putting theory into practice - Bekerian, D. A. (Oxford University Press, 2005)
For many students, the lecture hall or seminar room may seem vastly removed from the reality of everyday life. Applied Psychology: Putting Theory into Practice demystifies the link between the study of psychology, and psychology in the real world, illustrating how the application of psychology can be of benefit in many everyday settings.